Systematic review and meta-analysis of efficacy and safety of continuous positive airways pressure versus high flow oxygen cannula in acute bronchiolitis - Jefferson Antonio Buendía; John Edwin Feliciano-Alfonso; Mauricio Fernandez Laverde (BMC, 2022)
Abstract Introduction There are a trend towards increasing use of High-Flow Nasal Cannula (HFNC), outside of paediatric intensive care unit. Give this trend is necessary to update the actual evidence and to assess available published literature to determinate the efficacy of HFNC over Continuous Positive Air Pressure (CPAP) as treatment for children with severe bronchiolitis. Methods We searched MEDLINE, EMBASE, LILACS, and COCHRANE Central, and gray literature in clinical trials databases ( www.clinicaltrials.gov ), from inception to June 2022. The inclusion criteria for the literature were randomized clinical trials (RCTs) that included children < 2 years old, with acute moderate or severe bronchiolitis. All study selection and data extractions are performed independently by two reviewers. Results The initial searches including 106 records. Only five randomized controlled trial that met the inclusion criteria were included in meta-analysis. The risk of invasive mechanical ventilation was not significantly different in CPAP group and HFNC group [OR: 1.18, 95% CI (0.74, 1.89), I² = 0%] (very low quality). The risk of treatment failure was less significantly in CPAP group than HFNC group [OR: 0.51, 95% CI (0.36, 0.75), I² = 0%] (very low quality). Conclusion In conclusion, there was no significant difference between HFNC and CPAP in terms of risk of invasive mechanical ventilation. CPAP reduces de risk of therapeutic failure with a highest risk of non severe adverse events. More trials are needed to confirm theses results.